К вопросу о Концепции общегосударственной целевой программы развития промышленности Украины - Вишневский, В.П.; Збаразская, Л.А. (Економіка промисловості, 2013)
Запропоновано концептуальні положення щодо формування в Україні державної промислової політики матричного типу. Обґрунтовано доцільність неоіндустріального варіанта підйому промисловості в сучасних умовах розвитку на-
ціональної та світової економік. Рекомендовано шляхи та засоби вирішення завдань неоіндустріалізації у межах розробки і реалізації Загально-державної цільової програми розвитку промисловості на середньострокову перспективу.
Ключові слова: державне регулювання, промисловість, промислова політика, стратегія розвитку, цільова програма, неоіндустріалізація Предложены концептуальные положения формирования в Украине государственной промышленной политики матричного типа. Обоснована целесообразность неоиндустриального варианта подъема промышленности в современных условиях развития национальной и мировой экономик. Рекомендованы пути и средства решения задач неоиндустриализации в рамках разработки и реализации Общегосударственной целевой
программы развития промышленности на среднесрочную перспективу.
Ключевые слова: государственное регулирование, промышленность, промышленная политика, стратегия развития, целевая программа,
неоиндустриализация. The article covers the issues of conceptual modernization of national industrial policy of Ukraine. The timeliness of problem is determined by widespread deindustrialization induced by ineffective state regulation of the process of market-oriented reforms. At the same time, under the influence of the newest trends in global economics, in industrialized and faster growing countries an upsurge in interest in active state policy, based on new industrialization approach, is observed. Its idea consists in strengthening the own industry on the ground of the new technological base with the priority development of advanced industries.
The expedience of new industrial scenario of industrial development in Ukraine is determined by changes in production and markets structures in the world, shifts in international division of labor, development of new forms and practices of international competition and cooperation, and widespread changes in technology revolution. Keeping out of these trends Ukrainian industry risks to intrench itself between global industrial outsiders. It is proposed to solve that problem within a framework of matrix-type industrial policy. It allows combining efficiently the horizontal measures related to the development of favorable conditions for doing business in whole and specific forms and practices of their use for each industry. The new policies, such as the creation of favorable conditions for industrial development and development of high-quality institutional environment, promotion of innovations and development of advanced industries, maintenance of updated structural and sectoral goals of industrial development, are considered.
The partnership between state, business, science and society in the process of development of strategy of industrial development is reasonably required. The most acceptable form of its realization can be Nation-wide purpose-oriented program of industrial development. As efficient organizational tools of innovation processes acceleration it is proposed to apply the European experience regarding the development of Technology Platforms, Joint Technological Initiatives, scientific and production structures of cluster-type.
We substantiate the applicability of measures to facilitatethe entrance of domestic producers to global value chains in order to competitive growth. Among actions aimed to ameliorate the conditions of doing business we emphasizedthe priorities of taxation improvement, long-term lending, venture capital financing, facilitation of SME’s development, and maintenanceof the system of professional staff training.
Keywords: government regulation, industry, industrialpolicy, development strategy, purpose-oriented program, new industrialization.